State-space reduction in the model of Access Control Lists in IP routers. (9th February 2007) - Palugyai, Sandor; Csorba, Mate J.
This document provides an analytic performance model of routers using Access Control Lists (ACLs). For mathematical modelling, a Markovian process, the Discrete-Time Quasi Birth-Death (DQBD) process is used. ACLs in IP routers provide access control and protection for network segments and hosts. The mathematical model of ACLs that also includes input and output interface models is also introduced here, as well as an idea to reduce the state-space of the model, together with the corresponding proof.